Mechanism of frost heave cracking in PHC pipe piles: an experimental and numerical investigation - Zhang, Fa; Wu, Jianxin; Yin, Xiao; Jia, Mutian; Lacidogna, Giuseppe; Xu, Jie (Frontiers in Materials, 2025)
Vertical cracks in prestressed high-strength concrete (PHC) pipe piles caused by internal frost heaving endanger the safety and operational efficiency of photovoltaic facilities in cold regions. However, the underlying failure mechanisms remain insufficiently understood. This study investigates the cracking process by combining laboratory experiments with finite-element analysis (FEA) using the concrete damage plasticity (CDP) model. The results reveal a distinct cracking mechanism. In the experiment of this article, initiated at a temperature threshold of −5 °C to −8 °C, cracks consistently originate at the projection of prestressed tendons on the inner wall. These locations act as structural weak points where the concrete’s tensile strength is first exceeded. The subsequent failure is brittle, characterized by synchronous axial propagation and a guided, inside-out radial development along the tendons. A parametric analysis further reveals that increasing the concrete strength, axial prestress level, and wall thickness are effective strategies for enhancing cracking resistance by delaying both crack initiation and propagation. Applying external radial prestress is also a highly effective protective measure. The findings of this study can provide a basis for optimizing the anti-freezing design and protection of PHC piles.